Advances in Geothermal Energy - Ismail, Basel I. (IntechOpen, 2016)
Geothermal energy means the natural heat energy from the Earth. The geothermal resources of the Earth are huge and unlike other conventional and renewable energy sources, geothermal energy has unique features; namely, it is available, stable at all times throughout the year, independent of weather conditions, and has an inherent storage capability. Geothermal energy is also considered to be an environmentally friendly clean energy source that could significantly contribute to the reduction of GHG emissions. The utilization of geothermal energy is usually divided into the part used for electricity generation and the part used for heating applications. Due to its important utilization and future prospects, various interesting topics of research related to geothermal energy are covered in this book. This book is the result of contributions from several researchers and experts worldwide. It is hoped that the book will become a useful source of information and basis for extended research for researchers, academics, policy makers, and practitioners in the area of geothermal energy.